THE APPLICATION OF CORRUPTION LAW TOWARD CRIMINAL ACT IN THE FIELD OF FORESTRY - Ifrani Ifrani (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
In the practice occurduringthe handling corruption cases, it can be seen that the public prosecutor often encountered in the letter of indictment often use the Act 31 of 1999 jo Law No. 20 of 2001 to the other criminal offenses as criminal acts in the forestry, Law No. 20 of 2001 on Amendments to the Law No. 31 of 1999 on Corruption Eradication. In Article 14 explicitly states that the provision that: "Any personwho violates the provisions of the legislation expressly declare that the violation of the provisionsof the law as corruption apply the provisions stipulated in this law". It  means that such article of the Law on Corruption Eradication can be used to prosecute other crimes as criminal acts in the forestry, criminal acts in the banking, criminal acts in the taxation, and other crimes, as long as a criminal offense in the enactment laws related qualification as criminal offense corruption.